Evaluasi Kebugaran Jasmani Anggota Tarung Derajat Satlat Siginjai Berdasarkan Uji VO2MAX Via Website Topend Sports - Febriza, Nabil Afiqra; Hidayah, Krisvoniawati; Arisyi, Muhammad Fathan; Fauziyanti, Septiya; Yudiani, Walam; Widowati, Atri (SPRINTER: Jurnal Ilmu Olahraga, 2025)
Physical fitness plays a pivotal role in supporting athletic performance, particularly in high-intensity sports such as Tarung Derajat, which demands a combination of strength, speed, and endurance. This study aimed to evaluate the aerobic capacity of Tarung Derajat athletes from Satlat Siginjai by estimating their VO₂MAX using the indirect method of the 20-meter Shuttle Run Test (Beep Test). To enhance accuracy and efficiency, VO₂MAX values were calculated using an online calculator provided by the Topend Sports website. The research employed a quantitative descriptive approach involving 15 active members who met the inclusion criteria. Results indicated that the majority of participants fell into the "Fair" (46.7%) and "Poor" (13.3%) categories, while only 33.3% were classified as "Excellent" and 6.7% as "Good". These findings highlight a notable disparity in aerobic capacity among athletes. Consequently, training programs should prioritize the development of cardiovascular endurance through structured, evidence-based interventions. Regular fitness evaluations using validated instruments such as the Beep Test should be integrated into long-term training strategies to monitor progress and adjust training loads based on individual physiological needs.